Interleukin-35 Dampens CD8+ T Cells Activity in Patients With Non-viral Hepatitis-Related Hepatocellular Carcinoma - Yang, Lanlan; Shao, Xue; Jia, Shengnan; Zhang, Qian; Jin, Zhenjing (Frontiers in Immunology, 2019)
Interleukin (IL)-35 is a newly identified IL-12 cytokine family member, which has been demonstrated to induce immunotolerance by suppression of CD8+ T cells function in chronic viral hepatitis. However, the role of IL-35 in modulating CD8+ T cells activity in nonviral hepatitis-related hepatocellular carcinoma (HCC) was not fully elucidated. Forty-four patients with nonviral hepatitis-related HCC and twenty healthy individuals were enrolled. Serum IL-35 concentration was measured by ELISA. CD8+ T cells were purified from peripheral bloods and liver tissues. mRNA expression of cytotoxic/inhibitory molecules in CD8+ T cells with IL-35 stimulation was semi-quantified by real-time PCR. Direct and indirect contact co-culture systems of CD8+ T cells and HCC cell lines were set up. The modulatory function of IL-35 on peripheral and liver-resident CD8+ T cells was assessed by measurement of lactate dehydrogenase release and cytokine production in the co-culture supernatants. Serum IL-35 was notably elevated in HCC patients, while effective anti-tumor therapies down-regulated IL-35 concentration. Recombinant IL-35 stimulation suppressed cytotoxicity and proinflammatory cytokine secretion of peripheral and liver-resident CD8+ T cells in direct and indirect contact co-culture systems. This process was accompanied by reduction of perforin expression and interferon-γ production, as well as programmed death-1 and cytotoxic T-lymphocyte-associated protein 4 elevation in CD8+ T cells. The current data suggested that IL-35 inhibited both cytolytic and noncytolytic function of CD8+ T cells to nonviral hepatitis-related HCC probably via repression of perforin expression. IL-35 might be considered to be one of the therapeutic targets for patients with HCC.